Design of Hotspot Server Network Based on Mikrotik in Building Schools SMP Negeri 6 Banda Aceh - Zulfitriansyah, Zulfitriansyah; Muttaqin, Muttaqin (JOURNAL OF INFORMATICS AND COMPUTER SCIENCE, 2016)
Design of Mikrotik-Based Hotspot Server Network In School Building SMP Negeri 6 Banda Aceh aims to manage existing network connections with the Router. For Router management to fit the growing needs in an agency, need to be done by coding / script is quite complicated. SMP Negeri 6 Banda Aceh is an institution of educational unit. In the process of its development, especially in the field of Internet network requires adequate configuration. Without leaving the security system. By using Mikrotik RouterOSTM we can set router configuration by using Graphic User Interface (GUI) through Winbox facility so it is more User friendly. In addition Mikrotik also has facilities Bandwidth management and firewall that all that we can set in accordance with the needs on the computer network. The system development method that I use in developing this journal is Network Development Life Cycle (NDLC) method as it is in accordance with the subject of continuous computer network configuration which includes Analysis, Design, Simulation Prototype, Implementation, Monitoring and Management. Based on the monitoring produced, the configuration of the author Mikrotik do already meet the existing needs.Keywords: Mikrotik Router OS, Network Management, NDLC